The impact of government linked directors on firm performance: evidence from Oman - Elhabib, Mohamed Ateia (2015)
The presence of government-linked board members can be an effective corporate governance mechanism and a valuable resource for companies. The presence of such board members based on resource dependence theory is expected to enhance firm performance. This paper investigates the impact of government-linked board members in Oman on firm performance using Return on Assets and Tobin’s Q as proxy for firm performance. The findings of the study revealed that having a government linked board member such as a royal family member, a cabinet minister or a deputy minister on the board of a listed company have a positive but insignificant with firm performance as measured by both ROA and Tobin’s Q. However, statistical analysis show that the presence of a government representative as a board member has a positive impact on firm performance, as indicated by the positive coefficient for ROA and TOBINQ. An important implication of this result is that the presence of a government representative as a board member has a positive impact on firm performance, indicating that government employees board members is a valuable resource to the firm. This result is in line with the presumption of the resource dependence theory, that board members can act as a link between firms and access to valuable resource.(Hillman et al., 2009). Regulators such as Oman Capital Market Authority can use the study findings to issue recommendations to restructure boards in a way that some firms do not gain preferential treatment because of connection to government and political lobbyist.